RESISTENSI PRIMER MYCOBACTERIUM TUBERCULOSIS DENGAN TARGET Gen rpoB - Yunan Jiwintarum; Maruni Wiwin Diarti; Awan Dramawan (poltekkes kemenkes mataram, 2014)
Abstract: Detection of primary resistance in sputum samples of patients with pulmonary tuberculosis AFB (+) with molecular analysis on the target rpoB gene causes anti-tuberculosis drug resistance (OAT) rifampicin can be beneficial to the holder of a policy program to look for tuberculosis control efforts, one of attempt to overcome these problems is to deliver information about the resistance report in this interval. This research observasional descriptive study, the research variables Mycobacterium tuberculosis rpoB gene mutations and patients with pulmonary TB sputum smear (+), with the number of 50 sputum samples with acidental sampling technique. This study results showed all the samples (50 samples) microscopic examination of smear and PCR diagnostics with primary genes and gene Tb1-Tb2 results are positive (+) tuberculosis (100%). By nested PCR amplification techniques to prove that the primary gene rpoB1 negative results of 23 samples (46%), with the primary gene rpoB2 negative results in 13 samples (26%). Conclusion: A total of 13 samples (26%) occurred mutation in the gene rpoB / is resistant to the antibiotic rifampin.